Eritrea : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic developments in Eritrea during 1990-95. In 1993, despite strong growth in the industry and distribution sectors, real GDP growth was adversely affected by a substantial decline in agricultural output, owing to poor rain distribution, pest problems, and drought in some regions. The growth in industry reflected increased availability of raw materials and spare parts, and construction activity related to the rebuilding of war-damaged roads, buildings, and housing. The distribution sector benefited from the growth in the industrial sector as well as a substantial increase in imports.